Research Challenges in Homoeopathy - Taneja, Divya; Michael, James; Nayak, Chaturbhuj (Homœopathic Links, 2022)
Through this article, we attempt to identify and understand some of the major challenges in homoeopathic research and find solutions to overcome them. We have classified and compiled the challenges broadly under the headings of (1) conceptual challenges—difficulties in research arising due to conceptual differences between homoeopathy and conventional medicine, in the understanding of disease and its treatment; (2) methodological challenges—such as weak study designs, use of incorrect outcome measures, lack of knowledge of statistics, poor adherence to homoeopathic tenets leading to poor remedy selection etc.; (3) difficulties arising due to logistic challenges—lack of well-trained homoeopathic physicians in principles of homoeopathy as well as research, lack of proper infrastructure leading to hurdles such as limited access to research literature and other necessary resources; (4) research culture—these pertain to the difficulties in homoeopathic research stemming from the reluctance of the homoeopathic society to assimilate research into its culture. Some steps have been suggested to overcome these challenges, namely improving research education among homoeopathic fraternity, ensuring precise application of principles of homoeopathy as well as utilising correct research methodology, promoting interdisciplinary communication and encouraging interaction between academicians, researchers and practitioners and taking steps to improve the quality of documentation.
Keywords: AYUSH; CAM; challenges; homoeopathic research; research challenges